A cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide and a preparation method thereof
By mechanically alloying the porous polyaniline/reduced graphene oxide composite material with cobalt sulfur alloy, the problem of poor hydrogen storage performance of cobalt sulfur alloy is solved, and higher discharge capacity and cycle stability are achieved.
Patent Information
- Application Number
- CN202110262711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-11
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-03-11
AI Technical Summary
The existing cobalt sulfur alloys have poor hydrogen storage performance and low discharge capacity.
The porous polyaniline/reduced graphene oxide composite material and cobalt sulfur alloy are used for mechanical alloying to form a cobalt-sulfur hydrogen storage composite material containing porous polyaniline/reduced graphene oxide.
The discharge capacity and cycle stability of cobalt-sulfur hydrogen storage composite materials are improved, and the electrochemical hydrogen storage performance is enhanced.
Smart Images

Figure CN113054181B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials, and in particular relates to a method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide. Background Art
[0002] Hydrogen is extremely abundant in nature, clean and pollution-free, and is expected to become a major clean energy source in the future. However, hydrogen is not easy to store and is difficult to use on a large scale. Existing hydrogen storage and transportation methods are mainly divided into gaseous hydrogen storage, liquid hydrogen storage, and metal hydride solid hydrogen storage. Considering cost, safety and storage efficiency, metal hydride solid hydrogen storage has become a research hotspot.
[0003] From the current research results, it can be seen that the discharge capacity of Co-based hydrogen storage alloys has exceeded the theoretical discharge capacity of the current commercial rare earth hydrogen storage alloy AB5 type alloy (372mAh / g, LaNi5H6), and its cycle stability is much higher than that of Mg2Ni-based (AB type hydrogen storage alloy) hydrogen storage alloys. For example, Chung et al. prepared nanocrystalline ultrafine Co powder by chemical reduction and arc melting respectively. The maximum discharge capacity of the sample was above 410mAh / g. After 50 charge and discharge cycles, the discharge capacity was stable at about 350mAh / g, showing good cycle stability. Song et al. synthesized two novel Co-S microspheres by liquid phase chemical method and analyzed their formation mechanism. The Co-S nested spherical electrode has a current density of 200mAg -1 When it displays 250mAhg -1 The discharge capacity of Co-S alloy electrode is a reversible redox reaction of Co. Wang reported the synthesis of Co-S compound nanostructures with hierarchical structure by hydrothermal method and studied the electrochemical behavior of CoS with different morphological nanostructures as supercapacitor electrode materials. Qin et al. prepared pure Co9S8 and CoS2 powders with excellent cycle stability and hydrogen storage capacity by different ball milling times and speeds. After 100 cycles, the capacity retention rate was above 86%, and the electrochemical hydrogen storage capacity of the nanoparticles was 1.79wt% and 1.57wt%, respectively. Therefore, most cobalt-sulfur alloys have large-capacity hydrogen storage characteristics.
[0004] Adding conductive polymers to hydrogen storage materials is an effective way to improve the electrochemical properties of hydrogen storage materials, including discharge capacity and rate discharge capacity. On January 13, 2016, the Chinese Patent Office published the CN105237763A patent entitled "A method for synthesizing conductive polyaniline". The advantages of this invention are that polyaniline has good conductivity, simple product separation, energy saving and environmental protection, but the single-component polyaniline has a low specific surface area and poor electrochemical stability. Existing polyaniline composite materials usually use template method and original polymerization method to increase their surface area. For example, the CN108538613A patent entitled "A method for preparing a porous polyaniline electrode material with interconnected networks and controllable pores" published by the Chinese Patent Office on September 14, 2018 has the advantage that the silica sol used provides a template effect, and the controllability of the porous material structure is achieved by adjusting the amount of sol or its particle size.
[0005] In addition, the special structure of graphene determines its excellent properties, such as large specific surface area, high electron mobility, small mass density, high thermal stability and chemical stability. Conductive polymers, porous materials or graphene can improve the electrochemical properties of alloys. The representative patents disclosed by the Chinese Patent Office are shown in Table 1.
[0006]
[0007] If porous polyaniline and graphene are compounded, the synergistic effect of the two can be brought into play to improve the performance of the material, so that the composite material has both electrocatalytic effect and large specific surface area for application in the field of electrochemical hydrogen storage. In summary: Based on cobalt-sulfur hydrogen storage alloy, porous polyaniline / graphene composite material is added by mechanical alloying to obtain cobalt-sulfur hydrogen storage alloy material containing porous polyaniline / graphene and its manufacturing method, which has not been reported in patents or articles. Summary of the invention
[0008] The present invention aims to solve the technical problems of poor hydrogen storage performance and low discharge capacity of existing cobalt-sulfur alloys, and provides a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide and a preparation method thereof.
[0009] The present invention first provides a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which is self-assembled by graphene and porous polyaniline to form a 3D network structure, and is uniformly doped in a cobalt-sulfur alloy, and its expression is: Co9S8+x wt%PPANI / rGO, wherein 3≤x≤10.
[0010] The present invention also provides a method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which is carried out according to the following steps:
[0011] Step 1: Co metal powder and sublimated S powder are weighed in a molar ratio of 2:1, and are placed in a ball mill for 6 to 8 hours under a high-purity argon atmosphere. After the ball milling is completed, the ball mill is cooled to room temperature to obtain a cobalt-sulfur alloy with a chemical formula of Co9S8;
[0012] Step 2: Add concentrated HCl and aniline to a saturated salt solution, add a salt solution containing ammonium persulfate to the mixed solution, and keep it at room temperature for 4 hours. After filtering and washing with distilled water and acetone, porous polyaniline is obtained;
[0013] Step 3: The porous polyaniline obtained in step 2 was dissolved in NMP and heated at 50-60°C for 4-6 hours, and then the GO aqueous solution containing sodium ascorbate was added dropwise to the above solution, and the mixed solution was heated at 80-90°C for 2-3 hours. The gel was collected and dialyzed in pure water to remove impurities. After drying at 333K overnight, a porous polyaniline / reduced graphene oxide composite material was obtained;
[0014] Step 4: Put the porous polyaniline / reduced graphene oxide obtained in step 3 and the cobalt-sulfur alloy obtained in step 1 into a ball mill and mill them to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / graphene, wherein the ball-to-material weight ratio is (10-15):1, and the ball milling time is 1-10 min.
[0015] Preferably, the ball mill is a stainless steel ball mill.
[0016] Preferably, the diameter of the stainless steel ball is 4 to 15 mm.
[0017] Preferably, the vibration frequency of the ball mill is 200-1000 r / min.
[0018] Preferably, the ball-to-material weight ratio in step 1 is 10:1, and the ball milling time is 6 hours.
[0019] Preferably, the mass concentration ratio of the porous polyaniline and the reduced graphene oxide in step three is preferably 1:2.
[0020] Preferably, the weight percentage of PPANI / rGO and Co9S8 in step 4 is (3wt%~10wt%): (97wt%~90wt%).
[0021] Preferably, the ball-to-material weight ratio in step 4 is 10:1, and the ball milling time is 3 minutes.
[0022] Beneficial effects of the present invention
[0023] (1) A cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide of the present invention, wherein the material is a 3D network structure self-assembled by reduced graphene oxide and porous polyaniline, wherein the porous polyaniline / reduced graphene oxide composite enters the cobalt-sulfur material in the form of doping and is distributed on the surface of the grains, wherein the porous polyaniline can improve the electrocatalytic performance and reduce the volume change of the alloy, thereby maintaining the stability of the alloy, wherein the large specific surface area of the reduced graphene oxide can provide more active sites for the electrochemical reaction, and the synergistic effect of PPANI and rGO can accelerate the transmission of hydrogen, thereby improving the discharge capacity and life of the electrode;
[0024] (2) The present invention discloses a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide. The polyaniline / reduced graphene oxide composite is synthesized by a hydrothermal method, and the porous polyaniline / reduced graphene oxide is doped into the cobalt-sulfur alloy by a mechanical alloying method. The preparation process is simple, safe, and operable. The ball milling process can be controlled by adjusting the ball milling rate, ball-to-material ratio, and ball quality of the ball mill. Under the premise of ensuring that the cobalt-sulfur alloy structure is not destroyed, the porous polyaniline / reduced graphene oxide is successfully doped into the cobalt-sulfur alloy to form a hydrogen storage composite material containing porous polyaniline / reduced graphene oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of Co9S8 and the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4;
[0026] Figure 2 a is Co9S8, Figure 2 b is porous polyaniline, Figure 2 c is a scanning electron microscope image of the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Example 2;
[0027] Figure 3 The graph is a relationship curve between the simulated battery cycle number and the discharge capacity when Co9S8 and the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4 are used as negative electrode active materials. DETAILED DESCRIPTION
[0028] The present invention first provides a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which is self-assembled by reduced graphene oxide and porous polyaniline to form a 3D network structure, and is uniformly doped in a cobalt-sulfur alloy, and its expression is: Co9S8+x wt%PPANI / rGO, wherein 3≤x≤10.
[0029] The present invention also provides a method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which is carried out according to the following steps:
[0030] Step 1: Weigh Co metal powder and sublimated S powder in a molar ratio of 2:1, put them into a ball mill under a high-purity argon atmosphere, and mill them for 6 to 8 hours. After the ball milling is completed, the ball mill is cooled to room temperature to obtain a cobalt-sulfur alloy with a chemical formula of Co9S8;
[0031] Step 2: Add concentrated HCl and aniline to a saturated salt solution, add a salt solution containing ammonium persulfate to the mixed solution, and keep it at room temperature for 4 hours. After filtering and washing with distilled water and acetone, porous polyaniline is obtained;
[0032] Step 3: The porous polyaniline obtained in step 2 was dissolved in NMP and heated at 50-60°C for 4-6 hours, and then the GO aqueous solution containing sodium ascorbate was added dropwise to the above solution, and the mixed solution was heated at 80-90°C for 2-3 hours. The gel was collected and dialyzed in pure water to remove impurities. After drying at 333K overnight, a porous polyaniline / reduced graphene oxide composite material was obtained;
[0033] Step 4: Put the porous polyaniline / reduced graphene oxide obtained in step 3 and the cobalt-sulfur alloy obtained in step 1 into a ball mill and mill them to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, wherein the weight ratio of the ball to the material is (10-15):1, and the ball milling time is 1-10 min.
[0034] The present invention firstly weighs Co metal powder (purity 99.9%) and sublimed S powder (purity 99.5%) respectively according to a molar ratio of 2:1, puts them into a ball mill for ball milling for 6 hours under a high-purity argon atmosphere, the ball-material weight ratio is (10-15):1, preferably 10:1, the ball mill is preferably a stainless steel ball mill, the diameter of the stainless steel ball is preferably 4-15 mm, the vibration frequency of the ball mill is preferably 200-1000 r / min, and the ball mill is removed from the ball mill to obtain a cobalt-sulfur alloy;
[0035] Concentrated HCl and aniline are added dropwise to a saturated salt solution, and a salt solution containing ammonium persulfate is added dropwise to the mixed solution, and kept at room temperature for 4 hours. After filtering and washing with distilled water and acetone, a porous polyaniline is obtained;
[0036] The porous polyaniline was dissolved in NMP and heated at 50-60°C for 4-6 hours, and then the rGO aqueous solution reduced by sodium ascorbate was added dropwise to the above solution, and the mixed solution was heated at 80-90°C for 2-3 hours. The gel was collected and dialyzed in pure water to remove impurities. After drying at 333K overnight, a porous polyaniline / graphene composite material was obtained, wherein the mass concentration ratio of the porous polyaniline to rGO was preferably 1:2;
[0037] The porous polyaniline / reduced graphene oxide obtained above and the Co9S8 alloy obtained in step 1 are placed in a ball mill and ball milled to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, wherein the ball-to-material weight ratio is (10-15):1, preferably 10:1, and the ball milling time is 1-10 min, preferably 3 min. The weight percentage of the porous polyaniline / reduced graphene oxide and the cobalt-sulfur alloy is preferably (3wt%-10wt%): (97wt%-90wt%).
[0038] The phase structure of the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide of the present invention is characterized by X-ray diffraction (XRD). A Cu-Kα target is used in the test, the continuous scanning speed is 5° / min, and the scanning range is 10° to 80°.
[0039] The invention discloses a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide for electrochemical hydrogen storage performance test using a DC-5 battery tester, and the test process is carried out in a simulated nickel-hydrogen experimental battery. The battery manufacturing method is specifically as follows: the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide is used as an active material in a negative electrode of a nickel-hydrogen experimental battery, the active material is mixed evenly with 5 times the weight of carbonyl nickel powder as a current collector, and a tablet press is used to cold press a disc with a diameter of 10 mm and a thickness of 1.5 mm as the negative electrode of the battery, the tab of the negative electrode uses a nickel wire with a diameter of 1 mm and is connected to the negative electrode sheet by pulse spot welding, the positive electrode of the experimental battery uses commercial sintered nickel hydroxide (Ni(OH)2 / NiOOH), the diaphragm between the positive and negative electrodes uses a polypropylene diaphragm with good wettability and air permeability, and the electrolyte is a 6M KOH aqueous solution.
[0040] In order to further understand the present invention, the present invention is further described in detail below in conjunction with embodiments, but the present invention is not limited to these embodiments.
[0041] Example 1: Cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide Expression: Co9S8+3wt%PPANI / rGO, the material preparation method is as follows:
[0042] (1) 5.89 g of Co metal powder (purity 99.9%) and 3.21 g of sublimated S powder (purity 99.5%) were accurately weighed and placed in a stainless steel ball mill in a glove box filled with a high-purity argon atmosphere for ball milling. The steel ball diameter was 4 mm, the ball-to-material ratio was 10:1, the vibration frequency was 1000 r / min, and the ball milling time was 6 h. The ball mill was removed from the ball mill and opened in a high-purity argon atmosphere glove box to obtain a cobalt-sulfur alloy.
[0043] (2) 9 mL of concentrated HCl and 1.82 mL of aniline were added dropwise to 50 mL of saturated salt solution. 50 mL of salt solution containing 2.28 g of ammonium persulfate initiator was added dropwise to the mixed solution within 15 min and kept at room temperature for 4 hours. After filtering and washing with 500 mL of distilled water and 250 mL of acetone, pure porous polyaniline was obtained by drying at 60°C for 12 h.
[0044] (3) Accurately weigh 0.18 g of the porous polyaniline obtained in step (2) above and dissolve it in 6 mL of NMP, stir and heat at 50° C. for 4 hours to obtain a polyaniline stock solution (concentration of 30 mg / mL), disperse 1.8 g of multilayer graphene oxide in 30 mL of distilled water (concentration of 60 g / mL), then add 240 mg of sodium ascorbate to the GO aqueous solution, and add the mixed solution dropwise to the above polyaniline stock solution and heat at 90° C. for 2 hours. Collect the gel and dialyze it in pure water to remove impurities. After drying at 60° C. overnight, a porous polyaniline / reduced graphene oxide composite material is obtained.
[0045] (4) 1.94 g of Co9S8 and 0.06 g of porous polyaniline / reduced graphene oxide obtained in the above step (1) were accurately weighed respectively, and placed into a stainless steel ball mill in a glove box filled with a high-purity argon atmosphere for ball milling, with a steel ball diameter of 4 mm, a ball-to-material ratio of 10:1, a vibration frequency of 1000 r / min, and a ball milling time of 3 min. The ball mill was removed from the ball mill, and the ball mill was opened in a glove box with a high-purity argon atmosphere to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which was sealed and stored in a desiccator.
[0046] The XRD pattern of a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Example 1 is as follows: Figure 1 As shown, a Cu-Kα target was used in the test, the continuous scanning speed was 5° / min, and the scanning range was 10° to 80°.
[0047] Example 2: Cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide Expression: Co9S8+5wt%PPANI / rGO, the material preparation method is as follows:
[0048] Step (1) and steps (2) and (3) are the same as in Example 1;
[0049] (4) 1.9 g of the Co9S8 hydrogen storage alloy powder and 0.1 g of porous polyaniline / reduced graphene oxide obtained in the above step (1) were accurately weighed, respectively, and placed in a stainless steel ball mill in a glove box filled with a high-purity argon atmosphere for ball milling. The steel ball diameter was 4 mm, the ball-to-material ratio was 10:1, the vibration frequency was 1000 r / min, and the ball milling time was 3 min. The ball mill was removed from the ball mill and opened in a glove box with a high-purity argon atmosphere to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which was sealed and stored in a desiccator.
[0050] The XRD pattern of the second cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Example 2 is as follows: Figure 1 As shown, a Cu-Kα target was used in the test, the continuous scanning speed was 5° / min, and the scanning range was 10° to 80°.
[0051] Example 3: Cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide Expression: Co9S8+7wt%PPANI / rGO, the material preparation method is as follows:
[0052] Step (1) and steps (2) and (3) are the same as in Example 1;
[0053] (4) 1.86 g of Co9S8 and 0.14 g of porous polyaniline / reduced graphene oxide obtained in the above step (1) were accurately weighed respectively, and placed into a stainless steel ball mill in a glove box filled with a high-purity argon atmosphere for ball milling, with a steel ball diameter of 4 mm, a ball-to-material ratio of 10:1, a vibration frequency of 1000 r / min, and a ball milling time of 3 min. The ball mill was removed from the ball mill, and the ball mill was opened in a glove box with a high-purity argon atmosphere to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which was sealed and stored in a desiccator.
[0054] The XRD pattern of the second cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Example 3 is as follows: Figure 1 As shown, a Cu-Kα target was used in the test, the continuous scanning speed was 5° / min, and the scanning range was 10° to 80°.
[0055] Example 4: Cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide Expression: Co9S8+10wt%PPANI / rGO, the material preparation method is as follows:
[0056] Step (1) and steps (2) and (3) are the same as in Example 1;
[0057] (4) 1.8 g of the Co9S8 hydrogen storage alloy powder and 0.2 g of the porous polyaniline / reduced graphene oxide obtained in the above step (1) were accurately weighed, respectively, and placed in a stainless steel ball mill in a glove box filled with a high-purity argon atmosphere for ball milling. The steel ball diameter was 4 mm, the ball-to-material ratio was 10:1, the vibration frequency was 1000 r / min, and the ball milling time was 3 min. The ball mill was removed from the ball mill and opened in a glove box with a high-purity argon atmosphere to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, which was sealed and stored in a desiccator.
[0058] The XRD pattern of the second cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Example 4 is as follows: Figure 1 As shown, a Cu-Kα target was used in the test, the continuous scanning speed was 5° / min, and the scanning range was 10° to 80°.
[0059] Example 5
[0060] The cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4 and carbonyl nickel powder were respectively mixed uniformly in a weight ratio of 1:5, a pressure of 8 MPa was applied to the obtained powder mixture, and it was isotropically cold-pressed into a disc with a diameter of 10 mm and a thickness of 1.5 mm as the negative electrode. The tab of the negative electrode was made of nickel wire with a diameter of 1 mm and connected to the negative electrode sheet by pulse spot welding. The positive electrode of the nickel-hydrogen experimental battery was made of commercial sintered nickel hydroxide (Ni(OH)2 / NiOOH), and the separator between the positive and negative electrodes was a polypropylene separator with good wettability and air permeability. The electrolyte was a 6M KOH aqueous solution.
[0061] The performance of a simulated battery using the Co9S8 alloy and the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4 as the negative electrode active material was tested, specifically:
[0062] The improvement rate calculation formula is: capacity improvement rate = [(discharge capacity of "cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide" - discharge capacity of "blank battery for control") / discharge capacity of "blank battery for control"] × 100%.
[0063] The decay rate calculation formula is: capacity decay rate = [(maximum discharge capacity of the same battery - discharge capacity of the same battery at the 50th cycle) / maximum discharge capacity of the same battery] × 100%.
[0064] Figure 2 The surface morphologies of Co9S8 (Figure a), porous polyaniline (Figure b), and Co9S8+porous polyaniline / reduced graphene oxide (Figure c) are respectively.
[0065] Figure 3The figure is a curve diagram showing the relationship between the number of simulated battery cycles and the discharge capacity using Co9S8 and the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4 as the negative electrode active material. In the figure, curve 1 represents Co9S8, curve 2 represents Co9S8+3wt%PPANI / rGO, curve 3 represents Co9S8+5wt%PPANI / rGO, curve 4 represents Co9S8+7wt%PPANI / rGO, and curve 5 represents Co9S8+10wt%PPANI / rGO. It can be seen from the figure that the capacity changes of the five batteries are specifically shown in Table 2:
[0066]
[0067]
[0068] Table 2 shows the cycle stability performance data of the simulated battery with the Co9S8 alloy and the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide obtained in Examples 1 to 4 as the negative electrode active material. It can be seen from Table 2 that compared with the negative electrode of the Co9S8 alloy, the simulated battery with the cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide as the negative electrode active material of the present invention has excellent high-efficiency discharge performance, and when the content of porous polyaniline / reduced graphene oxide is 5wt%, the composite material has a maximum discharge capacity of 579.7mAh / g, and has better cycle stability than other composite materials. Continuing to increase the PPANI / rGO composite, the discharge capacity of the alloy decreases, because in the electrochemical reaction process, the excessive load of PPANI / rGO may cause the active material to separate from the alloy surface, thereby increasing the deactivation rate of the alloy electrode.
Claims
1. A cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, characterized in that The composite material is self-assembled by reduced graphene oxide and porous polyaniline to form a 3D network structure, and is uniformly doped in a cobalt-sulfur alloy. The composite material is expressed as Co9S8+x wt%PPANI / rGO, wherein 3≤x≤10.
2. A method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide as claimed in claim 1, characterized in that The method proceeds as follows: Step 1: Co metal powder and sublimated S powder are weighed in a molar ratio of 2:1, and ball-milled in a ball mill under a high-purity argon atmosphere to obtain a cobalt-sulfur alloy having a chemical formula of Co9S8. The ball milling time is 6 hours; Step 2: adding concentrated HCl and aniline dropwise into a saturated salt solution, adding a salt solution containing ammonium persulfate dropwise into the mixed solution, and keeping the mixture at room temperature for 4 hours, filtering and washing with distilled water and acetone to obtain porous polyaniline; Step 3: The porous polyaniline obtained in step 2 is dissolved in NMP and heated at 50-60° C. for 4-6 hours, and then the reduced graphene oxide aqueous solution obtained by reducing graphene oxide with sodium ascorbate is added dropwise to the NMP solution of the porous polyaniline, and the mixed solution is heated at 80-90° C. for 2-3 hours, the gel is collected and dialyzed in pure water to remove impurities, and after drying at 333K overnight, a porous polyaniline / reduced graphene oxide composite material is obtained; Step 4: Put the porous polyaniline / reduced graphene oxide obtained in step 3 and the cobalt-sulfur alloy obtained in step 1 into a ball mill and mill them to obtain a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide, wherein the ball milling time is 3 to 30 minutes.
3. The method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide according to claim 2, characterized in that: The ball mill described in step 1 and step 4 is a stainless steel ball mill with a ZrO2 lining.
4. The method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide according to claim 3, characterized in that: The stainless steel ball mill jar with ZrO2 lining has a vibration frequency of 200-1000 r / min.
5. The method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide according to claim 2, characterized in that: In the ball milling described in step 1 and step 4, the weight ratio of ball to material is (10-15):1, and the diameter of the ball is 4-15 mm.
6. The method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide according to claim 2, characterized in that: The mass concentration ratio of the porous polyaniline and reduced graphene oxide described in step three is 1:
2.
7. The method for preparing a cobalt-sulfur hydrogen storage composite material containing porous polyaniline / reduced graphene oxide according to claim 2, characterized in that: The weight percentages of the porous polyaniline / reduced graphene oxide and the cobalt-sulfur alloy described in step 4 are (3wt% to 10wt%): (97wt% to 90wt%).
Citation Information
Patent Citations
Synthetic method of conductive polyaniline
CN105237763A
Preparation method of porous polyaniline electrode materials with network intercommunication and controllable channels
CN108538613A
Co9S8 / graphene composite hydrogen storage material and preparation method thereof
CN104229731A
Preparation method of graphene polyaniline aerogel thermoelectric material
CN106046401A